Acute impacts from Teflon harnesses used to fit biologging devices to Black-legged Kittiwakes Rissa tridactyla. Issue 2 (3rd July 2021) - Clewley, G. D.; Cook, A. S. C. P.; Davies, J. G.; Humphreys, E. M.; O'Hanlon, N. J.; Weston, E.; Boulinier, T.; Ponchon, A.
ABSTRACT: Biologging is a routine technique for investigating movements and behaviours of birds in ecology, needing harnesses to attach devices to birds when long-term data of high spatial resolution are required. Evaluating the impacts on individuals of those devices and their attachment methods is important to maintain both animal welfare and the validity of data. In two independent trials of harnesses on Black-legged Kittiwake Rissa tridactyla, in Norway and the UK, harnesses were constructed from Teflon ribbon and deployed on breeding adults using two different attachment methods, a leg-loop (UK; n = 3) and thoracic cross-strap harness (UK; n = 3, Norway; n = 2). The birds were later recaptured and the harness fit and bird condition inspected. We found acute impacts from the harnesses of varying extent and severity, including abrasion and small lesions where the device or harness was sitting. Generally, the thoracic harness design caused more severe impacts, but some signs of feather abrasion were also evident on leg-loop individuals. While there was an apparently larger impact of thoracic harnesses on daily mass loss between recaptures compared with untagged or leg-loop individuals, the low sample sizes denied us statistically meaningful results. Continual appraisal in biologging studies is important, especially when studying a novel combination of species and attachment methods, even if those methods have been demonstrated to be safe and effective with similar taxa. Given the degree of abrasion reported here, we would not recommend the use of thoracic harnesses for Kittiwakes. However, leg-loops may be a viable alternative if different materials or design are used, provided that the impacts can be closely monitored and reported.